2018
DOI: 10.1002/adem.201800453
|View full text |Cite
|
Sign up to set email alerts
|

Substructure Development and Deformation Twinning Stimulation through Regulating the Processing Path during Multi‐Axial Forging of Twinning Induced Plasticity Steel

Abstract: Multi-axial forging (MAF) at room temperature is employed to investigate the effects of deformation processing path and the amount of imposed strain on the deformation mechanisms of a twinning-induced plasticity (TWIP) steel.The results indicate that the twin frequency is decreased by applying the 2nd compression ( P ɛ ¼ 0.8), however, an unexpected increase is realized at the end of first MAF pass ( P ɛ ¼ 1.2). This is attributed to the change in strain path and orientation dependence of deformation twinning.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…They found that the formation of nanograins, nanotwins, and segregation of solute to grain boundaries during HPT are responsible for enhanced strengthening. Akbarian et al [23] used multi-axial forging (MAF) at room temperature to process Fe-29.1Mn-0.039C-2.4Al-0.3Si TWIP steel, and investigated the mechanical properties and microstructural changes. Etemad et al [24] used accumulative roll bonding (ARB) to produce nano/ultrafine grain Fe-31Mn-3Al-3Si TWIP steel sheets at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the formation of nanograins, nanotwins, and segregation of solute to grain boundaries during HPT are responsible for enhanced strengthening. Akbarian et al [23] used multi-axial forging (MAF) at room temperature to process Fe-29.1Mn-0.039C-2.4Al-0.3Si TWIP steel, and investigated the mechanical properties and microstructural changes. Etemad et al [24] used accumulative roll bonding (ARB) to produce nano/ultrafine grain Fe-31Mn-3Al-3Si TWIP steel sheets at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Deformation twinning strongly depends on grain size and orientations, and more attention should be paid to microstructure and texture evolution caused by the severe deformation and plastic dissipation during FSSW/P of TWIP steel. Bimodal grain structures obtained during FSSW/P exhibit superior combination of strength and ductility through high work hardening capacity of coarse grains along with the strengthening ability of fine grains.…”
Section: Introductionmentioning
confidence: 99%